2019
DOI: 10.1016/j.chemphys.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of the thermal conductivity in nanofluids

Abstract: We evaluate the thermal conductivity of a model nanofluid at various volume fractions of nanoparticles with equilibrium (EMD) and non-equilibrium (NEMD) molecular dynamics simulations. The Green-Kubo formalism is used for the EMD simulations while a net heat flux is imposed on the system for the NEMD simulations. The nanoparticle-nanoparticle, fluid-fluid and fluid-nanoparticle interactions are all taken as Lennard-Jones potentials. An empirical parameter is added to the attractive part of the potential to con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In this study, the thermal conductivity variation for two different nanofluids was conducted without considering the variation in particle concentration. According to a recent study by Topal and Servantie [ 54 ], the incremental effect of nanoparticle concentration on the thermal conductivity is valid up to a certain range. However, at a certain point, the incremental effect of the thermal conductivity is halted.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the thermal conductivity variation for two different nanofluids was conducted without considering the variation in particle concentration. According to a recent study by Topal and Servantie [ 54 ], the incremental effect of nanoparticle concentration on the thermal conductivity is valid up to a certain range. However, at a certain point, the incremental effect of the thermal conductivity is halted.…”
Section: Discussionmentioning
confidence: 99%
“…Among the recent studies, Xu et al [ 23 ] investigated a novel method, called the improved steady-flow method, in determining the thermal conductivity of nanofluid and suggested that Al 2 O 3 -water nanofluid had great potential in the enhancement of thermal performance for a lower solid-volume fraction of nanofluid. Topal and Servantie [ 24 ] conducted a molecular dynamics simulation to calculate the thermal conductivity of nanofluids for various solid-volume fractions of nanofluids. They found enhanced thermal conductivity with a solid-volume fraction of 2%–3%.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating heat transfer in the vicinity of nanostructures immersed in water is of great importance for various applications. These applications cover the fields of biomedicine and thermal management. Illuminated colloidal metal nanostructures indeed provide tools for local nanoscale heat generation, with developments in solar energy conversion, and also for thermally assisted destruction of biological cells. , These processes all rely on the unique property of metallic nanoparticles to strongly absorb light in the vicinity of their plasmon resonance frequency . This extraordinary property opens the way for the generation of highly localized hot spots in a liquid environment.…”
Section: Introductionmentioning
confidence: 99%